Sleep and rest regulation in young and old oestrogen-deficient female mice. - Vyazovskiy, V; Kopp, C; Wigger, E; Jones, M; Simpson, E; Tobler, I (2006)
The effect of circulating oestrogen deficiency on sleep regulation and locomotor activity was investigated in aromatase cytochrome P450 deficient mice (ArKO) and wild-type (WT) controls. Sleep was recorded in 3-month old mice during a 24-h baseline day, 6-h sleep deprivation (SD) and 18-h recovery, and activity was recorded at the age of 3, 9 and 12 months. In mice deficient of oestrogen, the total amount of sleep per 24 h was the same as in WT controls. However, in ArKO mice, sleep was enhanced in the dark period at the expense of sleep in the light phase, and was more fragmented than sleep in WT mice. This redistribution of sleep resulted in a damped amplitude of slow-wave activity (SWA; power between 0.75-4.0 Hz) in non-rapid eye movement sleep across 24 h. After SD, the rebound of sleep and SWA was similar between the genotypes, suggesting that oestrogen deficiency does not affect the mechanisms maintaining the homeostatic balance between the amount of sleep and its intensity. Motor activity decreased with age in both genotypes and was lower in ArKO mice compared to WT at all three ages. After SD, the amount of rest in 3-month old WT mice increased above baseline and was more consolidated. Both effects were less pronounced in ArKO mice, reflecting the baseline differences between the genotypes. The results indicate that despite the pronounced redistribution of sleep and motor activity in oestrogen deficient mice, the basic homeostatic mechanisms of sleep regulation in ArKO mice remain intact.